POTENTIAL APPLICATIONS KEPAYANG COMBINATION OF SEEDS AND CELERY POWER ON DURABLE QUALITY AND CHICKEN WITH VARIATION OF FUTURE SAVE - Permata Ika Hidayati, Aju Tjatur Krisnaningsih, Yopi Hinggu Meha (Jurnal Sains Peternakan, 2017)
ABSTRACT This study aimed to determine the effect of kepayang and celery seed characteristics microbiological, chemical, and physical with a variety of fresh chicken meat shelf life. The material used in this research, namely meat, kepayang, celery. The meat used in this study as much as 1 kg, obtained from Malang Klojen market. Method of research done on the experiment using completely randomized design (CRD), which consists of 4 treatments, Po: 0 hours, P1: 24 hours, P2: 36 hours, P3: 72 hours, with each treatment was repeated 3 times. The research variables including TPC, protein testing, organoleptic test. Analysis of data using a single anava, if there is a difference then continued with LSD and Duncan. The results showed that with the addition of chicken meat preservation kepayang seeds and celery with a variety of shelf life provides a significant influence (P <0,01) against ALT and protein testing, with a low TPC values at 24 hours storage time is equal to 233,3cfu / g and the value of the highest protein levels at 72 hours of storage that is equal to 19.33%. In the organoleptic tests give a significant influence baset on the storage of 72 hours aroma of 7,9%, while based on the color and texture effect. The results of research carried out can be concluded that in the long storage time of 72 hours of application kepayang and celery seed blend provides the best quality of quality beef. For more research to do research using the test fat content, pH, water and using other types of meat. Keywords : seed kepayang, celery, total plate count, organoleptik, protein